USING GOOGLE CLASSROOM TO DEVELOP THE INSTRUCTIONAL IN MANAGEMENT LEARNING IN CLASSROOM FOR STUDENTS OF THE FACULTY OF EDUCATION, CHIANG RAI RAJABHAT UNIVERSITY - Srevichai, Suthasinee; Thita, Sairung; Ariya, Kritiya (Journal of Social Science and Cultural, 2024)
The main purpose of this research was to study the result of using Google Classroom to develop the instructional in Management Learning in Classroom subject for student in Education Faculty and the secondary purpose were to compare the student achievement before and after this experiment and to study student satisfaction after using Google classroom of this experiment. The population of this research were 47 students who registered in Management Learning in Classroom Subject that focuses on content in developing teachers' professional competencies in the second semester of 2020 academic year. The research tools were learning plan by using Google Classroom, Meet and Application of Google for Education for 18 weeks throughout the semester, Pre-Post achievement test and the satisfaction assessment form after using Google Classroom of student in Education Faculty, after that the researcher analyzed all data for the percentage, mean and standard deviation of the scores obtained. The result of research were the study results of the achievement by using Google classroom to develop the instruction in management learning in classroom found the average of pre-test was 14.64 and the standard deviation was 3.84 and the average of post-test was 33.18 and the standard deviation was 4.35 and comparing scores pre-test and post-test found that post-test score was higher than pre-test score criterion at the .01 level of statistic significance. And the study results of overall student satisfaction who received learning activities after using Google Classroom had the highest level , the average was 3.90 and the standard deviation was 0.66